Kemudahan Penggunaan dan Harga Terhadap Minat Beli Online Konsumen - Hapsawati Taan (e-Journal Ekonomi Bisnis dan Akuntansi, 2021)
The purpose of this study was to determine the effect of ease of use and price on consumer buying interest on the Shopee online shopping site. escriptive quantitative type approach. The population used is people who have made online purchases at the Shopee online store. Population infinity, the number of samples used was 83 respondents. The unit of analysis is students of the Faculty of Economics, State University of Gorontalo. Non-probability sampling method with accidental sampling method. The results showed that ease of use had a positive and significant effect on consumer buying interest online. Price has a positive and significant effect on purchase intention. Ease of use and price simultaneously influence purchase intention. The most dominant influence is the price variable. Another implication is that Shopee online store management leaders or Shopee online policy makers should consider further about policies that can increase Shopee's online buying interest.